Aberrant expressions of miRNA-206 target, FN1, in multifactorial Hirschsprung disease - Gunadi (Orphanet J Rare Dis, 2019)
BACKGROUND: MicroRNAs (miRNAs) have been associated with the Hirschsprung disease (HSCR) pathogenesis, however, the findings are still inconclusive. We aimed to investigate the effect of miRNA-206 and its targets, fibronectin 1 (FN1), serum deprivation response (SDPR), and paired box 3 (PAX3) expressions on multifactorial HSCR in Indonesia, a genetically distinct group within Asia. METHODS: We determined the miRNA-206, FN1, SDPR and PAX3 expressions in both the ganglionic and aganglionic colon of HSCR patients and control colon by quantitative real-time polymerase chain reaction (qRT-PCR). RESULTS: Twenty-one sporadic HSCR patients and thirteen controls were ascertained in this study. The miRNA-206 expression was up-regulated (2-fold) in the ganglionic colon and down-regulated (0.5-fold) in the aganglionic colon compared to the control group (ΔC(T) 12.4 ± 3.0 vs. 14.1 ± 3.9 vs. 13.1 ± 2.7), but these differences did not reach significant levels (p = 0.48 and p = 0.46, respectively). Interestingly, the FN1 expression was significantly increased in both the ganglionic (38-fold) and aganglionic colon (18-fold) groups compared to the control group ΔC(T) 5.7 ± 3.0 vs. 6.8 ± 2.3 vs. 11.0 ± 5.0; p = 0.001 and p = 0.038, respectively). Furthermore, the expressions of SDPR were similar in the ganglionic, aganglionic and control colon groups (ΔC(T) 2.4 ± 0.6 vs. 2.2 ± 0.4 vs. 2.1 ± 0.6; p = 0.16 and p = 0.39, respectively), while no change was observed in the PAX3 expression between the ganglionic, aganglionic, and control colon groups (ΔC(T) 3.8 ± 0.8 vs. 4.1 ± 0.8 vs. 3.7 ± 1.1; p = 0.83 and p = 0.44, respectively). CONCLUSION: Our study is the first report of aberrant FN1 expressions in the colon of patients with HSCR and supplies further insights into the contribution of aberrant FN1 expression in the HSCR pathogenesis.